Diagnostic Implications of Enhanced CD34 Expression in Hepatocellular Carcinoma: A Cross-Sectional Study - Sofia Waheed Khan, Fabiha Moeen, Shoaib Anwar, Mariam Ijaz, Ayesha Anwar, Faisal Naeem Bandesha, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hepatocellular carcinoma is the most prevalent primary cancer of the liver globally and is responsible for the majority of cancer-related fatalities. The purpose of the research was to establish the frequency of enhanced cd34 expression in sinusoid-like vascular endothelial cells in Hepatocellular carcinoma. Methods: CMH Multan's Department of Histopathology carried out a cross-sectional study. Histochemical staining was performed. Before beginning the staining technique, sections were washed in phosphate buffer saline for 5 minutes. The usual immunohistochemistry staining method - Avidin Biotin Complex Method - was employed following hospital protocols. Results: 85 (67.5%) male and 41 (32.5%) female patients were among the 126 studied cases. 54 (42.9%) were from rural areas, while 72 (57.1%) were from urban areas. Diabetes was prevalent in 43 (34.1%), and smoking was found in 10 (7.9%). Obesity was found in 18 (14.3%), and hypertension was identified in 74 (58.7%). Only 5 (4.0%) of our research's cases had a family history of HCC. Enhanced cd34 expression was noted in 106 (84.1%). Conclusion: There found a very high frequency of enhanced cd34 expression of sinusoid-like vascular endothelial cells in HCC. The enhanced cd34 presentation can aid in the early recognition of HCC and the proper care of these patients to improve their quality of life. Keywords: Enhanced Expression, Hepatocellular carcinoma, cd34, Risk factors.